Analysis of the Training of Future Engineers-Educators to Databases Design - Korzhova, Mariya (Pedagogical Discourse, 2013)
The paper analyzes the characteristics of teaching the subject «Principles of Information Security and databases» in terms of the training of future engineers and educators; it elucidated components of professional activity on designing databases and consider the substantive and procedural components of the profession of the future engineers and educators to design databases based on program course «Principles of information Security and databases» and professional experts in database design.